2014
DOI: 10.1155/2014/745640
|View full text |Cite
|
Sign up to set email alerts
|

CUDT: A CUDA Based Decision Tree Algorithm

Abstract: Decision tree is one of the famous classification methods in data mining. Many researches have been proposed, which were focusing on improving the performance of decision tree. However, those algorithms are developed and run on traditional distributed systems. Obviously the latency could not be improved while processing huge data generated by ubiquitous sensing node in the era without new technology help. In order to improve data processing latency in huge data mining, in this paper, we design and implement a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 16 publications
(15 reference statements)
0
15
0
1
Order By: Relevance
“…No performance results are reported. Another decision tree construction algorithm is described in Lo et al (2014). They report speedups of 5-55Â over WEKA's Java-based implementation of C4.5 (Quinlan, 2014), called J48, and 18Â over SPRINT.…”
Section: Building Tree Classifiers On Gpusmentioning
confidence: 99%
“…No performance results are reported. Another decision tree construction algorithm is described in Lo et al (2014). They report speedups of 5-55Â over WEKA's Java-based implementation of C4.5 (Quinlan, 2014), called J48, and 18Â over SPRINT.…”
Section: Building Tree Classifiers On Gpusmentioning
confidence: 99%
“…As for the GPU platform, we used the NVidia Geforce Titan (876 MHz, 2,496 CUDA cores, and 6GB DDR5 off-chip memory) with the same processor and the main memory running on the Ubuntu 14.04 LTS. To generate the executable code, first, we generated the RF by the scikit-learn, then, we used the CUDA Tree (CU-DAT) [13] to generate the executable code. To measure the LPS, we used 1,000 random test vectors, while to measure the power consumption excluding the idle power, we inserted the power measurement between the host PC and the power source.…”
Section: Compared With Other Platformsmentioning
confidence: 99%
“…Win-Tsung Lo [5] et al, have designed and implement a new parallelized decision tree algorithm on a CUDA (compute unified device architecture), which is a GPGPU solution provided by NVIDIA where CPU is responsible for flow control while the GPU is responsible for computation. Andrea Dal Pozzolo [6] et al, have shown how Hellinger Distance Decision Trees can be successfully applied in unbalanced and evolving stream data by removing instance propagations between batches.…”
Section: Current Approaches In Decision Treesmentioning
confidence: 99%